Contemporary type 1 diabetes pregnancy outcomes: impact of obesity and glycaemic control. Issue 4 (15th August 2016) - Abell, Sally K; Boyle, Jacqueline A; de Courten, Barbora; Knight, Michelle; Ranasinha, Sanjeeva; Regan, John; Soldatos, Georgia; Wallace, Euan M; Zoungas, Sophia; Teede, Helena J
Abstract: Objective: To compare contemporary pregnancy outcomes in women with and without type 1 diabetes, and to examine the effects of obesity and glycaemic control on these outcomes. Design and setting: Historical cohort study in a specialist diabetes and maternity network in Victoria. Participants: All singleton births (at least 20 weeks' gestation), 2010–2013, were analysed: 107 pregnancies to women with type 1 diabetes and 27 075 pregnancies to women without diabetes. Women with type 2 diabetes or gestational diabetes were excluded. Methods: Data were extracted from the Birthing Outcomes System database; associations between type 1 diabetes and pregnancy outcomes were analysed by multivariable regression. Main outcome measures: Mode of birth; maternal and neonatal outcomes. Results: The mean body mass index was higher for women with type 1 diabetes than for women without diabetes (mean, 27.3 kg/m 2 [SD, 5.0] v 25.7 kg/m 2 [SD, 5.9]; P = 0.01); the median gestation period for their babies was shorter (median, 37.3 weeks [IQR, 34.6–38.1] v 39.4 weeks [IQR, 38.4–40.4]; P < 0.001) and they were more likely to be large for gestational age (LGA) (adjusted odds ratio [aOR], 7.9; 95% CI, 5.3–11.8). Women with type 1 diabetes were more likely to have had labour induced (aOR, 3.0; 95% CI, 2.0–4.5), a caesarean delivery (aOR, 4.6; 95% CI, 3.1–7.0), or a pre‐term birth (aOR, 6.7; 95% CI, 4.5–10.0); their babies were more likely to have shoulder dystocia (aOR, 8.2; 95% CI, 3.6–18.7), hypoglycaemia (aOR, 10.3; 95% CI, 6.8–15.6), jaundice (aOR, 5.1; 95% CI, 3.3–7.7), respiratory distress (aOR, 2.5; 95% CI, 1.4–4.4) or to suffer perinatal death (aOR, 4.3; 95% CI, 1.9–9.9). In women with type 1 diabetes, greater obesity was associated with increased odds for an LGA baby or congenital malformation, and increased HbA1c levels were associated with pre‐term birth and perinatal death. Conclusion: Women with type 1 diabetes, even when managed in a specialist setting, still experience adverse obstetric and neonatal outcomes. Poor glycaemic control is not wholly responsible for adverse outcomes, reinforcing the importance of other risk factors, such as obesity and weight gain.